English as a Lingua Franca in an Indonesian Multilingual Setting: Pre-Service English Teachers’ Perceptions - Silalahi, Ronald Maraden Parlindungan; Santoso, Wulandari; Hutauruk, Bertaria Sohnata (REiLA : Journal of Research and Innovation in Language, 2023)
The notion of English as Lingua Franca (ELF) has challenged the English as a Foreign Language (EFL) paradigm, which mainly aimed to attain native-like competence. Generally, ELF-informed teaching promotes creative use of English in a multilingual environment to meet communication needs. It also emphasises intelligibility in ELF spoken communication rather than pursuing standard English only. This study aimed to examine the perceptions of Indonesian pre-service English teachers regarding ELF. Using the sequential explanatory design, this study distributed close-ended questionnaire items to 150 participants in the first stage of data collection, followed by Focus Group Discussion (FGD) with five participants in the second stage. Descriptive statistics and thematic analyses were used to explore the research data quantitatively and qualitatively. The results of this study demonstrated that the participants still favoured the English native-speaker model in teaching English. They believed that students should imitate English native speakers in communication. The findings of the qualitative data analysis, however, showed that their perceptions towards ELF were still constrained by the ideological rankings between native English and other varieties of English. This study suggests that ELF-informed teaching should be introduced and reflected in teacher preparatory programmes, so that it could develop future English teachers’ awareness of the importance of implementing the principles of ELF in the Indonesian educational setting.